Edukasi Hipertensi terhadap Pengetahuan, Kepatuhan Minum Obat, dan Tekanan Darah pada Pasien Hipertensi (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the effectiveness of hypertension education on the level of knowledge, adherence to medication, and blood pressure in hypertensive patients. This research method is Quasi-Experimental, with the design being One-group pre-test and post-test. The results showed that the level of knowledge, adherence to taking medication, and blood pressure were p=0.000 (p